Efeito da Quimosina associada ao Lactobacillus Rhamnosus EM1107 nas características nutricionais do soro de leite caprino - Pereira, Neusa Lygia Vilarim (2020)
Goat whey is a bioproduct of the soluble fraction of milk, rich in proteins, peptides, lactose, water-soluble vitamins and minerals, obtained from the processing of cheeses, through the coagulation of casein, which can be: enzymatic, acidic and mixed. In obtaining the milk gel and whey, the kind of processing and the kind of milk used influence the physical-chemical, nutritional and sensory aspects of these products. Despite these characteristics, it is still rejected by producers, which makes it a waste with a high environmental impact. In this study, the effect of chymosin associated with Lactobacillus rhamnosus EM1107 on nutritional composition, on the profile of carbohydrates, organic acids, minerals, protein and amino acid of goat whey was evaluated. Pasteurized milk was subjected to two different treatments from which two kinds of goat whey originated: Treatment 1 obtained W1 (goat whey obtained from the coagulation of casein by the action of the animal enzyme - chymosin) and Treatment 2 obtained if W2 (goat whey obtained from the coagulation of casein by the action of chymosin and the probiotic Lactobacillus rhamnosus EM1107). Whey were stored under refrigeration temperature (4 ± 1 ° C), at times 1, 15 and 30 days, each time being subjected to lyophilization and analysis. Treatment W2 was evaluated for the viability of the probiotic microorganism and both treatments were evaluated for physical-chemical composition, carbohydrate profile, organic acids, minerals, protein and amino acids. The multiplication of L. rhamnosus in W2 was observed during storage, with counts ranging from 8.23 to 8.82 log UFC mL-1. This microbial multiplication resulted in a reduction in lactose levels, with a higher production of lactic acid, mainly after the 15th day of storage in W2 (p≤0.05). These data were confirmed from the analysis of the profile of sugars and organic acids, in which lower values of the disaccharide lactose and glucose were observed, which may prove the greater consumption of these sugars as an energy source for the fermentation process of L. rhamnosus EM1107. Concomitantly, higher levels of lactic, acetic and succinic acid were found in W2, detecting the increase in acidity content during storage. Both wheys didn‟t show statistical difference for GOS (p> 0.05). Ca, followed by Mg, were the minerals in greatest concentration, with emphasis on W2. The increase in microbial count (p≤0.05) also caused a reduction in protein levels, an increase in the degree of hydrolysis, protein consumption and hydrolysis, an increase in free amino acids and the formation of peptides with a greater hydrophilic character. Both treatments had amino acid content that met FAO/WHO standards, with emphasis on W2. α-Lactoalbumin and β-Lactoglobulin remained in all treatments and at all times. Both matrices have peculiarities in their composition that can be preponderant in determining their application, and can be used as a bioactive ingredient for the formulation of several functional food products, in addition to acting as a delivery food matrix, since it keeps in viable counts the Lactobacillus rhamnosus EM1107 microorganism during storage.